KAJIAN LITERATUR: SUNAT PEREMPUAN DITINJAU DARI ASPEK UMUM DAN KESEHATAN - Fitri Kurniati; Fitri Fujiana; Uray Fretty Hayati (Jurnal Ilmu Keperawatan, 2022)
Background: Female genital mutilation raises pros and cons among the community because of its impact. There are still many parents who perform genital mutilation on their daughters. In addition, some parents choose not to circumcise their daughters. Objective: To analyze the general impact and health impact of female genital mutilation. Methods: a literature review by searching related articles through the Google Scholar database, Researchget and Science Direct. The keywords used in Indonesian are "sunat” and "perempuan" and "dampak" while in English, they are "female" and "genital mutilation" or "circumcision" and "consequences". The search found seven related articles which were then analyzed in a narrative review. Result: Female genital mutilation impacts health, including bleeding, bacterial infection, urinary tract infection, complications during childbirth, tetanus and shock. In addition to health problems, female circumcision is also associated with early marriage. Female circumcision is also called a tradition and an act that violates human rights. Conclusion: All articles reviewed explained that female genital mutilation harms general health and well-being. Female circumcision can harm the woman herself. It is hoped that nurses will provide more comprehensive education to the community regarding the dangers and impacts of female circumcision. Keywords: female circumcision, female genital mutilation, the impact of female genital mutilation